2000
DOI: 10.1021/jp993016o
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Double Proton Transfer in the CHX−XH···CHX−XH (X = O, S) Complexes

Abstract: A theoretical study of double-proton-transfer processes in bimolecular complexes formed by combinations of molecules of the type CHX−XH (X = O, S) is reported. The reactions are rationalized in terms of the energy, chemical potential, and hardness of hydrogen-bonded and isolated species. Sanderson's rule to determine molecular chemical potential and hardness from the values of the constituent fragments is used to characterize the relaxation effects due to hydrogen bonding. In ten formation and seven double-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
133
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(141 citation statements)
references
References 60 publications
(114 reference statements)
7
133
0
1
Order By: Relevance
“…Chemical potential characterizes the tendency of electrons to escape from the equilibrium distribution and is related to Mulliken's [39] electronegativity (χ) [36,[39][40][41][42][43]. Molecular hardness can be understood as a resistance to change the equilibrium electronic distribution [36,[39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical potential characterizes the tendency of electrons to escape from the equilibrium distribution and is related to Mulliken's [39] electronegativity (χ) [36,[39][40][41][42][43]. Molecular hardness can be understood as a resistance to change the equilibrium electronic distribution [36,[39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hardness can be understood as a resistance to change the equilibrium electronic distribution [36,[39][40][41][42][43]. Through the finite difference approximation and Koopman's [44] theorem working formulae for μ and η in terms of ionization potential (IP) and electron affinity (EA) [36,45], energies of the frontier molecular orbitals (FMOs) HOMO and LUMO (ε H and ε L ) are obtained:…”
Section: Introductionmentioning
confidence: 99%
“…Esta herramienta ha sido usada para probar varios sistemas moleculares. [5][6][7][8] El estudio teórico en el modelo de la Teoría de Funcionales de la Densidad, puede ayudar como una guía en la reactividad de los halobencenos. La Teoría de Funcionales de la Densidad es un modelo conceptual para relacionar los cálculos con conceptos tales como potencial químico electrónico (μ), 9-12 dureza química (η) 9-13 y electrofilicidad (ω), 14 conceptos que nos ayudan a entender el comportamiento electrónico de los sistemas.…”
Section: Introductionunclassified
“…Both principles have been applied successfully to the study of molecular vibrations, 9,15-18 internal rotations, 6͑b͒,19 excited states, 20,21 aromaticity, 22 and different types of chemical reactions. 12,[23][24][25][26][27][28][29][30][31][32][33] It has been found in most of these cases that the conditions of maximum hardness and minimum polarizability complement the minimum energy criterion for molecular stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, relaxation of these constraints seems to be permissible, and in particular, it has been found that in most cases the MHP still holds even though the chemical and external potentials vary during the molecular vibration, internal rotation or along the reaction coordinate. 12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Hereafter, we will refer to the generalized MHP ͑GMHP͒ or MPP ͑GMPP͒ as the maximum hardness or minimum polarizability principles that do not require the constancy of chemical and external potentials during molecular change. It is worth emphasizing that the generalized versions of these principles have not been proven.…”
Section: Introductionmentioning
confidence: 99%